2024
DOI: 10.37978/tijfs.v3i2.55
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: A Risk Factor of Preeclampsia

Abstract: Background: Obesity is a major epidemic of developed world that is now extending to developing countries and is the risk factor of pre-eclampsia which is the major contributor to maternal and foetal morbidity & mortality. Objective: To determine the frequency of preeclampsia in obese primigravida women visiting the Obstetrics and Gynaecology Outpatient Department of Bahawal Victoria Hospital, Bahawalpur, Pakistan. Methodology: This cross-sectional descriptive study was conducted in Obstetrics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Thus, in our study we found a direct proportional association between the PE development and an increased BMI before pregnancy, even in overweight; however, the association with the obesity degree has not been demonstrated. This is consistent with the conclusions of other authors [7][8][9][10].…”
Section: Resultssupporting
confidence: 94%
“…Thus, in our study we found a direct proportional association between the PE development and an increased BMI before pregnancy, even in overweight; however, the association with the obesity degree has not been demonstrated. This is consistent with the conclusions of other authors [7][8][9][10].…”
Section: Resultssupporting
confidence: 94%
“…Numerous scientific studies have concluded that older age (35 years) and an increase in BMI before pregnancy (25 kg/m 2 ) are considered moderate risk factors for PE [25][26][27][28][29][30][31]. A high rate of PE is associated with the study selection of pregnant women with maternal risk factors according to FIGO recommendations [5].…”
Section: Discussionmentioning
confidence: 99%